Discourse Markers Usage and Challenges in Students’ Writing of Procedure Text - Mullynanda Pontiaka; Diah Kristina; Endang Setyaningsih (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The objective of this study is to analyze how vocational students use discourse markers in writing procedure text. Moreover, this study tends to address students’ challenges in using discourse markers to write the text. The study used qualitative content analysis. To collect the data, documentation and interviews were chosen as the technique. The results are elaborative discourse markers are the most used type among four types by Fraser’s (2005) categorization. It is also found that students’ challenges are students’ unfamiliarity with discourse markers and its’ meaning in Indonesian. It is concluded that the study support previous researches’ statement about discourse markers usage is related with students’ competence.